Role of ADAMTS13 in Pathogenesis of ST-Elevation Myocardial Infarction in Iraqi Patients - Oudha, Haneen A. A.; Al-Khateeb, Shatha M. J.; Al-Haideri, Ahmed Q. J. (Scientific Journal of Medical Research, 2022)
Background: ST-elevation myocardial infarction (STEMI) is a medical condition characterized by myocardial ischemia symptoms in the presence of prolonged ECG-ST elevation (STE) and the consequent release of myocardial necrosis biomarkers. The ADAMT disintegrin-like metalloproteinases with thrombospondin type 1 motifs are a family of proteinase enzymes detected within the ECM and plasma. The ADAMT family consists of nineteen enzymes with different functions. Aims: To examine the sequence of changes in the levels o a disintegrin and Metalloprotease with Thrombo-Spondin motif (ADAMTS13 throughout ST-elevation myocardial infarction and to see how they relate to other cardiovascular risk factors in Iraqi patients Materials and Methods: The study design is a case-control study. The present study is a casecontrol study comprised of 42 subjects of the patients with st-elevation myocardial infraction cases and 48 apparently healthy as control groups. The sample was collected from Karbala heart center in the AL-Imam AL_Hussein medical city in the period from20-1-2021 to 1-3- 2021, the parameters is done worked in the laboratory of AL-Imam AL_Hussein medical city. Results: The current study observed a weak positive relationship between ADAMT with VWF, HS Troponin T, and CK-MB with P-value ?0.05. There is a strong positive relationship between TC, LDL, and HDL with p-value >0.001 and ADAMT, and a weak negative relationship between VLDL, TG, and B.sugar with ADAMT. The median levels of the VWF level were higher in ST-elevation MI patients compared to the control group with p-value ? 0.001 and reduced level ADAM with p-value =0.01 Conclusion: The current study is a case-control study comprised of 42 subjects of the patients who have st-elevation myocardial infractions as cases and 48 apparently healthy as control groups. There was observed a weak positive relationship between ADAMT with VWF, HS Troponin T, and CK-MB with p-value ?0.05, and a strong positive relationship between TC, LDL, and HDL with p-value >0.001 and ADAMT, and a weak negative relationship between VLDL, TG, and B.sugar with ADAMT. The median levels of the VWF level were higher in ST-Elevation MI patients compared to the control group with p-value ? 0.001 and reduced level ADAM with p-value = 0.01.